Nature and community-based tourism (CBT) for poverty alleviation: a case study of Lower Kinabatangan, East Malaysia - Ching, Goh Hong (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Ecological tourism is intimately associated with natural features such as scenic beauty, beaches and marine areas, flora and fauna, parks and conservation areas. Increasingly, this tourism is organized to help in the cause of rural poverty alleviation through community-based initiatives. This study illustrates this CBT trend in East Malaysia. Data were collected from field interviews with 208 villagers of Kampung Perpaduan, Kampung Batu Puteh, Kampung Mengaris and Kampung Singgah Mata involved in ecological tourism activities in Batu Puteh, Lower Kinabatangan River of Sabah. The findings of the paper reaffirmed the rationales for community-based tourism which not only aimed at poverty alleviation and enhancement of local community participation, but also underlined the role of the natural environment in community based tourism (CBT). They revealed how the holistic, sustainable approach of integrating a rural development project with forest conservation efforts and profit-oriented tourism business could be achieved by working with multiple stakeholders at various levels of operation.